Efficacy of cyclin-dependent-kinase 9 inhibitors in a murine model of mixed-lineage leukemia - Garcia-Cuellar, M-P; Füller, Elisa; Mäthner, Emanuel; Breitinger, Constanze; Hetzner, Katrin; Zeitlmann, L.; Borkhardt, A.; Slany, Robert (Leukemia, 2014)
Mixed-lineage leukemia fusion proteins activate their target genes predominantly by stimulating transcriptional elongation. A core component necessary for this activity is cyclin-dependent kinase 9. Here we explored the effectiveness of small molecules targeting this enzyme as potential therapeutics. A screen of seven compounds with anti-CDK9 activity applied to a panel of leukemia cell lines identified flavopiridol and the experimental inhibitor PC585 as superior in efficacy with inhibitory concentrations in the submicromolar range. Both substances induced rapid dephosphorylation of the RNA polymerase II C-terminal domain, accompanied by downregulation of CDK9-dependent transcripts for MYC and HOXA9. Global gene expression analysis indicated the induction of a general stress response program, culminating in widespread apoptosis. Importantly, colony-forming activity in leukemia lines and primary patient samples could be completely inhibited under conditions that did not affect native precursors from bone marrow. In vivo application in a mouse transplant model significantly delayed disease with PC585 showing also oral activity. These results suggest CDK9 inhibition as novel treatment option for mixed-lineage leukemia. © 2014 Macmillan Publishers Limited.
Keywords: CDK9; inhibitor; mixed-lineage leukemia; preclinical study

Insulin-like growth factor 1 is a direct HOXA9 target important for hematopoietic transformation - Steger, Julia; Füller, Elisa; Garcia-Cuellar, Maria-Paz; Hetzner, Katrin; Slany, Robert (Leukemia, 2015)
HOX homeobox proteins are key oncogenic drivers in hematopoietic malignancies. Here we demonstrate that HOXA1, HOXA6 and predominantly HOXA9 are able to induce the production of insulin-like growth factor 1 (Igf1). In chromatin immunoprecipitations, HOXA9 bound directly to the putative promoter and a DNase-hypersensitive region in the first intron of the Igf1 gene. Transcription rates of the Igf1 gene paralleled HOXA9 activity. Primary cells transformed by HOXA9 expressed functional Igf1 receptors and activated the protein kinase Akt in response to Igf1 stimulation, suggesting the existence of an autocrine signaling loop. Genomic deletion of the Igf1 gene by Cre-mediated recombination increased sensitivity toward apoptosis after serum starvation. In addition, the leukemogenic potential of Igf1-negative, HOXA9-transformed cells was impaired, leading to a significant delay in disease development on transplantation into recipient animals.

Pbx3 and Meis1 cooperate through multiple mechanisms to support Hox-induced murine leukemia - Garcia-Cuellar, Maria-Paz; Steger, Julia; Füller, Elisa; Hetzner, Katrin; Slany, Robert (Haematologica, 2015)
Hox homeobox transcription factors drive leukemogenesis efficiently only in the presence of Meis or Pbx proteins. Here we show that Pbx3 and Meis1 need to dimerize to support Hox-induced leukemia and we analyze the molecular details of this cooperation. In the absence of Pbx3, Meis1 was highly unstable. As shown by a deletion analysis Meis1 degradation was contingent on a motif coinciding with the Pbx-binding domain. Either deletion of this sequence or binding to Pbx3 prolonged the half-life of Meis1 by preventing its ubiquitination. Meis1 break-down could also be blocked by inhibition of the ubiquitin proteasome system, indicating tight post-transcriptional control. In addition, Meis1 and Pbx3 cooperated genetically as overexpression of Pbx3 induced endogenous Meis1 transcription. These functional interactions translated into in vivo activity. Blocking Meis1/Pbx3 dimerization abrogated the ability to enhance proliferation and colony-forming cell numbers in primary cells transformed by Hoxa9. Furthermore, expression of Meis1 target genes Flt3 and Trib2 was dependent on Pbx3/Meis1 dimerization. This correlated with the requirement of Meis1 to bind Pbx3 in order to form high affinity DNA/Hoxa9/Meis1/Pbx3 complexes in vitro. Finally, kinetics and severity of disease in transplantation assays indicated that Pbx3/Meis1 dimers are rate-limiting factors for Hoxa9-induced leukemia.

The interaction of ENL with PAF1 mitigates polycomb silencing and facilitates murine leukemogenesis - Hetzner, Katrin; Garcia-Cuellar, Maria-Paz; Büttner, Christian; Slany, Robert (Blood, 2018)
Eleven-nineteen leukemia (ENL) is a chromatin reader present in complexes stimulating transcriptional elongation. It is fused to mixed-lineage leukemia (MLL) in leukemia, and missense mutations have been identified in Wilms tumor and acute myeloid leukemia. Here we demonstrate that ENL overcomes polycomb silencing through recruitment of PAF1 via the conserved YEATS domain, which recognizes acetylated histone H3. PAF1 was responsible for antirepressive activities of ENL in vitro, and it determined the transforming potential of MLL-ENL. MLL-ENL target loci showed supraphysiological PAF1 binding, hyperubiquitination of histone H2B and hypomodification with H2AUb, resulting in accelerated transcription rates. YEATS mutations induced a gain of function, transforming primary hematopoietic cells in vitro and in transplantation assays through aberrant transcription and H2B ubiquitination of Hoxa9 and Meis1 Mechanistically, H3 and PAF1 competed for ENL interaction, with activating mutations favoring PAF1 binding, whereas the MLL moiety provided a constitutive PAF1 tether allowing MLL fusions to circumvent H3 competition.
EVALuna2:34633